Analisis Kemampuan Guru SMP dalam Mengintegrasikan Nilai-Nilai Islami pada Pembelajaran Seni (Studi Penelitian di MTsS Darul Ulum Banda Aceh dan SMP IT Al-Fityan Aceh Besar) - Zulkarnaen Zulkarnaen (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Art learning as one of the sciences taught in schools must be able to answer the challenge that Islamic values education can be taught through learning in class. The fact shows that art learning which has been carried out in schools is considered less effective. The purpose of this study was to determine the teacher's ability, the application process and the supporting and inhibiting factors in integrating Islamic values in art learning. This research use desciptive qualitative approach. Data obtained by interview, observation and documentation. The research informants were school principals, curriculum representatives, art teachers, and students at MTsS Darul Ulum Banda Aceh and SMPIT Al-Fityan Aceh Besar. The results of the study show the teacher's ability to integrate Islamic values in art learning: (a) MTsS Darul Ulum Banda Aceh; Teachers find it difficult to find Islamic values that are exactly equivalent to material concepts. (b) SMPIT Al-Fityan Aceh Besar; The teacher is able to relate Islamic values by following the hadith references narrated by Bukhari and Muslim. The implementation process carried out: (a) MTsS Darul Ulum Banda Aceh; at the discussion stage the teacher tries to associate it with Islamic values. (b) SMPIT Al-Fityan Aceh Besar; The teacher tries to explain points about the afterlife messages as well as Islamic teachings. Supporting factors include the educational environment that combines general education and Islamic boarding school education, while the inhibiting factors are the teacher's ability level, which still has difficulties in integrating material.